2005
DOI: 10.1099/ijs.0.63254-0
|View full text |Cite
|
Sign up to set email alerts
|

Methanobacterium beijingense sp. nov., a novel methanogen isolated from anaerobic digesters

Abstract: Two methanogenic strains, 8-2T and 4-1, with rod-shaped (0?4-0?563-5 mm), non-motile cells, sometimes observed in chains, were isolated from two anaerobic digesters in Beijing, China. The two strains used H 2 /CO 2 and formate for growth and produced methane. The temperature range for growth was 25-50 6C, with fastest growth at 37 6C. The pH ranges for growth and methane production were 6?5-8?0 for strain 8-2 T and 6?8-8?6 for strain 4-1, with the fastest growth at pH 7?2 for strain 8-2 T and pH 7?5-7?7 for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
76
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(77 citation statements)
references
References 28 publications
0
76
0
1
Order By: Relevance
“…The cultivated, recognized species that appeared most closely related to strain 17A1 T , with a 16S rRNA gene sequence similarity of 96.3 %, was Methanobacterium beijingense 8-2 T (Ma et al, 2005). Since its 16S rRNA gene sequence showed ,97 % similarity with the corresponding sequences of recognized species of the genus Methanobacterium, strain 17A1 T should be considered to represent a novel species (Stackebrandt & Goebel, 1994).At the time of writing, the genus Methanobacterium comprised 19 species with validly published names (Bonin & Boone, 2006;Kitamura et al, 2011;Krivushin et al, 2010;Ma et al, 2005;Mori & Harayama, 2011;Shcherbakova et al, 2011;Shlimon et al, 2004;Zhu et al, 2011). These species usually grow by reducing CO 2 with H 2 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The cultivated, recognized species that appeared most closely related to strain 17A1 T , with a 16S rRNA gene sequence similarity of 96.3 %, was Methanobacterium beijingense 8-2 T (Ma et al, 2005). Since its 16S rRNA gene sequence showed ,97 % similarity with the corresponding sequences of recognized species of the genus Methanobacterium, strain 17A1 T should be considered to represent a novel species (Stackebrandt & Goebel, 1994).At the time of writing, the genus Methanobacterium comprised 19 species with validly published names (Bonin & Boone, 2006;Kitamura et al, 2011;Krivushin et al, 2010;Ma et al, 2005;Mori & Harayama, 2011;Shcherbakova et al, 2011;Shlimon et al, 2004;Zhu et al, 2011). These species usually grow by reducing CO 2 with H 2 .…”
mentioning
confidence: 99%
“…The 16S rRNA genes of the novel strain and cloned isolates from the sediments of the dystrophic Lake Grosse Fuchskuhle (Chan et al, 2002; GenBank accession number AF481340) and the meromictic Lake Kinneret (Nüsslein et al, 2001; AJ310872) were found to be similar (.97 % sequence similarity). The cultivated, recognized species that appeared most closely related to strain 17A1 T , with a 16S rRNA gene sequence similarity of 96.3 %, was Methanobacterium beijingense 8-2 T (Ma et al, 2005). Since its 16S rRNA gene sequence showed ,97 % similarity with the corresponding sequences of recognized species of the genus Methanobacterium, strain 17A1 T should be considered to represent a novel species (Stackebrandt & Goebel, 1994).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The dominant clones were most closely related to Methanobacterium beijingense (AY350742), Methanosae ta harundinacea (AY970347), and Methanosaeta concilii (M59146). M. beijingense, a methanogen recently isolated from an anaerobic digester, can utilize H 2 /CO 2 or formate to form methane, but not acetate (Ma et al 2005). In contrast, M. harundinacea, a microorganism isolated from a UASB reactor treating brewery wastewater (Ma et al 2006), and M. concilii, a methanogen commonly found in anaerobic reactors (Ekiel et al 1985;Patel and Sprott 1990), are obligate acetoclastic methanogens.…”
Section: Archaea Clone Librariesmentioning
confidence: 99%